Benzo[a]pyrene represses DNA repair through altered E2F1/E2F4 function marking an early event in DNA damage-induced cellular senescence. Issue 21 (9th November 2020) - Allmann, Sebastian; Mayer, Laura; Olma, Jessika; Kaina, Bernd; Hofmann, Thomas G; Tomicic, Maja T; Christmann, Markus
Abstract: Transcriptional regulation of DNA repair is of outmost importance for the restoration of DNA integrity upon genotoxic stress. Here we report that the potent environmental carcinogen benzo[a]pyrene (B[a]P) activates a cellular DNA damage response resulting in transcriptional repression of mismatch repair (MMR) genes ( MSH2, MSH6, EXO1) and of RAD51, the central homologous recombination repair (HR) component, ultimately leading to downregulation of MMR and HR. B[a]P-induced gene repression is caused by abrogated E2F1 signalling. This occurs through proteasomal degradation of E2F1 in G2-arrested cells and downregulation of E2F1 mRNA expression in G1-arrested cells. Repression of E2F1-mediated transcription and silencing of repair genes is further mediated by the p21-dependent E2F4/DREAM complex. Notably, repression of DNA repair is also observed following exposure to the active B[a]P metabolite BPDE and upon ionizing radiation and occurs in response to a p53/p21-triggered, irreversible cell cycle arrest marking the onset of cellular senescence. Overall, our results suggest that repression of MMR and HR is an early event during genotoxic-stress induced senescence. We propose that persistent downregulation of DNA repair might play a role in the maintenance of the senescence phenotype, which is associated with an accumulation of unrepairable DNA lesions.